2021
DOI: 10.1002/bse.2788
|View full text |Cite
|
Sign up to set email alerts
|

Does quality management improve the internalization of environmental practices? An empirical study in Africa

Abstract: This article analyzes the role of quality management in the internalization of environmental practices. A qualitative study based on interviews with 35 practitioners was conducted in three African countries (Cameroon, Senegal, and Ivory Coast). The results highlight the contrasting roles played by the main reference model for quality management-International Organization for Standardization (ISO) 9001-in the internalization of the international standard for corporate environmental management-ISO 14001-with pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Thereby, the efficiency of sequentially implementing different MSs is increased, ultimately resulting in a high degree of integration (Bernardo et al, 2017). Tayo Tene et al (2021) showed that the prior adoption of ISO 9001 promoted the internalization of ISO 14001 practices. Bernardo et al (2018) also showed that the internalization of IMS gives firms more benefits.…”
Section: Positive Effects Of Integration Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, the efficiency of sequentially implementing different MSs is increased, ultimately resulting in a high degree of integration (Bernardo et al, 2017). Tayo Tene et al (2021) showed that the prior adoption of ISO 9001 promoted the internalization of ISO 14001 practices. Bernardo et al (2018) also showed that the internalization of IMS gives firms more benefits.…”
Section: Positive Effects Of Integration Strategiesmentioning
confidence: 99%
“…Firms that engage in the continuous internalization of quality management practices can establish a long-term strategic perspective and pursue short-term performance goals (Sroufe and Curkovic, 2008). This parallel approach contributes to the internalization of future EMS practices (Tayo Tene et al, 2021;Wiengarten and Pagell, 2012) and the consequent increase in performance benefits (Bernardo et al, 2015). and Simon and Douglas (2013) found that organizations that have adopted all QMS þ EMS strategies are able to derive more IJOPM 43,2 internal benefits from IMS, such as task simplification, organizational efficiency improvements, organizational culture improvements and better utilization of audit results.…”
Section: Positive Effects Of Integration Strategiesmentioning
confidence: 99%
“…More critical approaches have highlighted that the measures implemented are often superficial and that organizations engage in greenwashing practices (Guo et al, 2020;Marquis et al, 2016;Talbot & Boiral, 2018;van Halderen et al, 2016). These measures are not necessarily intended to substantially change practices and improve performance but rather to appear legitimate in the eyes of stakeholders by taking actions that are often symbolic and superficial (Cho et al, 2015;Perego & Kolk, 2012;Tayo Tene et al, 2021). The lack of coherence between companies' empathic messaging about the urgency of climate issues and the practices they actually put into place shows the importance of transparent carbon reporting, which can be defined as a set of quantitative and qualitative information that relates to a firm's past and forecasted carbon emissions levels; its exposure to and financial implications of climate change associated risk and opportunities; and its past and future actions to manage these risks and opportunities.…”
Section: The Institutionalization Of Carbon Reportingmentioning
confidence: 99%